Analisa Dan Perancangan Mobile APP Unit Pengaduan Masyarakat Pada Dinas Perindustrian Dan Perdagangan Provinsi Sumatera Utara - takhir, Said; Jasmir; Fachruddin (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
Abstract− The public complaint system is an important medium in accommodating aspirations, criticisms, and complaints from the public regarding public services. However, the complaint process at the Industry and Trade Service of North Sumatra Province is still carried out manually, making it less effective and efficient in terms of recording, monitoring, and following up on complaints. This study aims to analyze the needs and design an Android-based mobile application system for the Public Complaints Unit to facilitate the process of submitting and handling complaints. The system development method used is Waterfall, with design tools in the form of UML (Unified Modeling Language) such as use case diagrams, activity diagrams, and class diagrams. The results of this study are a complaint application design that can help improve the quality of public services by providing a structured complaint flow, documented complaint data storage, and follow-up notifications to users.